MicroRNAs in Hearing Disorders: Their Regulation by Oxidative Stress, Inflammation and Antioxidants - Prasad, Kedar N.; Bondy, Stephen C. (Frontiers in Cellular Neuroscience, 2017)
MicroRNAs (miRs) are small non-coding single-stranded RNAs that bind to their complimentary sequences in the 3’-untranslated regions (3’-UTRs) of the target mRNAs that prevent their translation into the corresponding proteins. Since microRNAs are strongly expressed in cells of inner ear and play a role in regulating their differentiation, survival and function, alterations in their expression may be involved in the pathogenesis of hearing disorders. Although increased oxidative stress and inflammation are involved in initiation and progression of hearing disorders, it is unknown whether the mechanisms of damage produced by these biochemical events on inner ear cells are mediated by altering the expression of miRs. In neurons and non-neuronal cells, reactive oxygen species (ROS) and pro-inflammatory cytokines mediate their damaging effects by altering the expression of miRs. Preliminary data indicate that a similar mechanism of damage on hair cells produced by oxidative stress may exist in this disease. Antioxidants protect against hearing disorders induced by ototoxic agents or adverse health conditions; however, it is unknown whether the protective effects of antioxidants in hearing disorders are mediated by changing the expression of miRs . Antioxidants protect mammalian cells against oxidative damage by changing the expression of miRs. Therefore, it is proposed that a similar mechanism of protection by antioxidants against stress may be found in hearing disorders. This review discusses novel concepts: (a) alterations in the expression of miRs may be involved in the pathogenesis of hearing disorders, (b) presents evidence from neurons and glia cells to show that oxidative stress and pro-inflammatory cytokines mediate their damaging effects by altering the expression of miRs; and proposes that a similar mechanism of damage by these biochemical events may be found in hearing loss, and (c) present data to show that antioxidants protect mammalian cells against oxidative by altering the expression of miRs,. A similar role of antioxidants in protecting against hearing disorders is put forward. New studies are proposed to fill the gaps in the areas listed above.